2022
DOI: 10.1108/ajems-06-2022-0244
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between electronic human resource management and employee job satisfaction in organizational value-creation in Africa: the case of Zimbabwe

Abstract: PurposeThe purpose of this paper is to examine the mediating effect of employee job satisfaction on the relationship between electronic human resource management (e-HRM) use and e-HRM macro-level consequences.Design/methodology/approachData were collected through a survey involving 32 organizations, using e-HRM applications. A purposive sampling technique was employed. A structural equation modeling technique with the use of the process macro approach was used to analyze collected data.FindingsE-HRM use has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Several studies have examined this relationship, providing evidence of the important role that self-organizational capabilities play in promoting resilience in microfinance institutions. For example, in a study by Ngwenya and Khumalo (2018), they found that self-organizational capabilities, such as the ability to adapt to changing circumstances and innovate, were important factors in promoting resilience in microfinance institutions in Zimbabwe. The authors argue that self-organization enables institutions to respond to challenges such as economic downturns and changes in regulations, leading to greater resilience.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined this relationship, providing evidence of the important role that self-organizational capabilities play in promoting resilience in microfinance institutions. For example, in a study by Ngwenya and Khumalo (2018), they found that self-organizational capabilities, such as the ability to adapt to changing circumstances and innovate, were important factors in promoting resilience in microfinance institutions in Zimbabwe. The authors argue that self-organization enables institutions to respond to challenges such as economic downturns and changes in regulations, leading to greater resilience.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that investing in e-HRM contributes to desirable outcomes ( (Nyathi & Kekwaletswe, 2024). In this study, participants were asked to share their insights on how e-HRM adoption could contribute to achievement of desirable outcomes.…”
Section: Qualitative Research Findingsmentioning
confidence: 99%
“…The E-HRM system was evaluated by a 6-item scale adapted from Nyathi and Kekwaletswe [63]. For instance, we incorporated statements such as "I have the necessary knowledge to use the e-HRM system" and "The e-HRM system helps me improve my job performance".…”
Section: Questionnaire Design and Study Measuresmentioning
confidence: 99%